Effects of photobiomodulation therapy in patients with chronic non-specific low back pain: protocol for a randomised placebo-controlled trial. Issue 10 (24th October 2017) - Tomazoni, Shaiane Silva; Costa, Lucíola da Cunha Menezes; Guimarães, Layana de Souza; Araujo, Amanda Costa; Nascimento, Dafne Port; Medeiros, Flávia Cordeiro de; Avanzi, Marina Athayde; Costa, Leonardo Oliveira Pena
Abstract : Introduction: Low back pain (LBP) is one of the largest and most frequent public health problems worldwide. Photobiomodulation therapy (PBMT) is a frequently used non-pharmacological therapy for the treatment of musculoskeletal disorders. However, there is little high-quality scientific evidence that demonstrates the effectiveness of PBMT in the treatment of patients with chronic LBP in the short, medium and long term. Therefore, the objective of this clinical trial is to evaluate the effects of PBMT in patients with chronic non-specific LBP in the short, medium and long term. Methods and analyses: This is a prospectively registered, two-arm randomised placebo-controlled trial with blinded patients, assessors and treatment providers. One hundred and forty-eight patients with chronic non-specific LBP will be recruited. Treatment sessions will be provided three times a week for 4 weeks (totaling 12 sessions) with patients receiving either placebo or active PBMT. For ethical reasons, all patients, regardless of treatment allocation, will also receive an information booklet based on 'The Back Book'. Clinical outcomes will be measured at baseline, at the end of treatment, as well as 3, 6 and 12 months after randomisation. The primary outcomes will be pain intensity and disability measured after 12 sessions of treatment. The secondary outcomes will be pain intensity and disability measured at 3, 6 and 12 months after randomisation, in addition to specific disability and global perceived effect in all time points. Ethics and dissemination: The study was approved by the Research Ethics Committee of Universidade Cidade de São Paulo. The results will be disseminated through scientific publications and presentations at national and international scientific meetings. Trial registration number: NCT03089424 .